Thank you for the opportunity to help you with your question!
To solve this problem, you first need to distribute the outer numbers to the inner numbers of the parentheses. A general formula for this principle would look like this: a(b+c)=a*b+a*c. Be careful with the positives and negatives though. Another general formula: a(b-c)=a*b-a*c. Now when 'a' is negative: -a(b+c)=-a*b-a*c
-2(x+6)+3(2x-5)=3(x-4)+10 Distribute terms.
-2x-12+6x-15=3x-12+10 Now combine 'like' terms.
4x-27=3x-2 Get the 'x' terms on one side to solve for x.
Please let me know if you need any clarification. I'm always happy to answer your questions.